Enhanced photocatalytic activity of C, F-codoped TiO2 loaded with AgCl - Yan, Hongjian; Kochuveedu, Saji Thomas; Quan, Li Na; Lee, Sang Soo; Kim, Dong Ha (ELSEVIER SCIENCE SA, 2013)
A protocol is reported for the development of a unique type of a co-doped TiO2 with two kinds of non-metal atoms, carbon (C) and fluorine (F), as a visible-light active photocatalyst system. C, F-codoped TiO2 nanoobjects with anatase phase were synthesized by calcination of a mixture of TiOF2 and sulfuric-acid-treated melamine. The C, F co-doping resulted in a red-shift of the absorption edge to 510 nm from the 390-nm value obtained for a control TiO2 photocatalyst. The C, F-codoped TiO2 shows photocatalytic activity under visible light irradiation. Furthermore, the loading of AgCl into the parent co-doped TiO2 enhanced its activity for degradation of methylene blue dye by about 3.5 times in the first hour irradiation. A brief mechanism responsible for the enhancement is proposed in terms of the transfer of holes from C, F-codoped TiO2 to the AgCl phase. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: EXPOSED 001 FACETS; SOL-GEL METHOD; VISIBLE-LIGHT; ANATASE TIO2; DOPED TIO2; CALCINATION TEMPERATURE; TITANIUM-DIOXIDE; NANOPARTICLES; PERFORMANCE; EFFICIENT